2013
DOI: 10.4049/jimmunol.1203029
|View full text |Cite
|
Sign up to set email alerts
|

Selective Impairment of P2Y Signaling by Prostaglandin E2 in Macrophages: Implications for Ca2+-Dependent Responses

Abstract: Extracellular nucleotides have been recognized as important modulators of inflammation via their action on specific pyrimidine receptors (P2). This regulation coexists with the temporal framework of proinflammatory and proresolution mediators released by the cells involved in the inflammatory response, including macrophages. Under proinflammatory conditions, the expression of cyclooxygenase-2 leads to the release of large amounts of PGs, such as PGE2, that exert their effects through EP receptors and other int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 73 publications
6
35
0
Order By: Relevance
“…Moreover, other studies have shown that lipid mediators can interact with P2Y receptors. Recently, it was reported that PGE 2 selectively impairs P2Y receptor-mediated Ca 2+ mobilization (31). Other works have demonstrated that pulmonary inflammation mediated by LTE 4 requires P2Y12 receptor (32).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other studies have shown that lipid mediators can interact with P2Y receptors. Recently, it was reported that PGE 2 selectively impairs P2Y receptor-mediated Ca 2+ mobilization (31). Other works have demonstrated that pulmonary inflammation mediated by LTE 4 requires P2Y12 receptor (32).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate here that CD73 upregulation on CD14 C cells by sPE is blocked by inhibiting its receptors, EP2 and EP4, confirming the role of PGE 2 in the regulation of the adenosinergic pathway in mesothelioma. PGE 2 has also been shown to impair purinergic signaling by ATP in macrophages 36 which suggests that in the presence of PGE 2 , extracellular ATP is preferentially undergoing hydrolysis by myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence was recorded at 510 nm in an LS50B Perkin-Elmer spectrofluorometer (PerkinElmer, Norwalk, CT) provided with continuous stirring and using a dual excitation source at 340 and 380 nm. The maximal and minimal fluorescence of the assay were determined for each sample after addition of 1% SDS and 5 mM EGTA (pH 9), respectively (29).…”
Section: Camentioning
confidence: 99%